A family to save the doctor's heart - Lennox, Marion (Harlequin medical romance, 2022)
A lesson from the gorgeous doc: A family can be the greatest gift! A year ago Jenny was an emergency doctor, loving life in fast-paced Sydney. Now, after the loss of her brother and his wife, she's living an unrecognizable life on remote Albatross Island, raising her nieces and nephews. Then Dr. Silas washes up on her beach, shipwrecked and injured! Just like Jenny and the kids, Silas is no stranger to grief. But can he bring hope to Jenny and her fledgling family, too?